Rancang Bangun Pengering Gabah Tabung Vertikal Dengan Bahan Bakar Tempurung Kelapa - Jamal Jamal; Tri Agus Susanto; Dermawan Dermawan; Al Fajri Nur Rohman; Jusman Jusman; Muhammat Firdaus (Jurnal Sinergi Jurusan Teknik Mesin, 2023)
Drying grain using direct sunlight is still widely practiced in Indonesia. This method has an obstacle, namely that it is very dependent on solar conditions, apart from that, it also disrupts traffic flow because they often use the highway as a place to dry. In this research, a vertical tube dryer was developed using coconut shell fuel. Coconut shells are unused agricultural waste, this dryer can also use other fuels which become agricultural waste. The test results of the vertical tube dryer can speed up grain drying, from the manual method which takes 6-7 hours to 7-10 minutes with a grain weight of 5-10 kg. able to reduce water content from 27.3% to 13.6% (according to standard) in 7.9 minutes for a grain weight of 5.5 kg.